2012
DOI: 10.1631/jzus.b1100049
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity relationships of antimicrobial fatty acids and derivatives against Staphylococcus aureus

Abstract: Fatty acids and derivatives (FADs) are resources for natural antimicrobials. In order to screen for additional potent antimicrobial agents, the antimicrobial activities of FADs against Staphylococcus aureus were examined using a microplate assay. Monoglycerides of fatty acids were the most potent class of fatty acids, among which monotridecanoin possessed the most potent antimicrobial activity. The conventional quantitative structure-activity relationship (QSAR) and comparative molecular field analysis (CoMFA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…It is worthy to mention that the antimicrobial activity of donkey milk significantly decreased (38-40%) after digestion with pepsin (2 mg/ml) and kept about 60 to 62 % of its antimicrobial activity against B. cereus and S. aurous, respectively, suggesting that the fatty acids of donkey milk has the majority of the antimicrobial effect ( Figure 2). Similar results were reported that monoglycerides of fatty acids possessed the most potent antimicrobial activity against S. aureus [19]. It has been indicated that, donkey's native and digested milk have different effects against two pathogenic bacterial strains; Escherichia coli and Listeria monocytogenes [20].…”
Section: Chemical Composition and Antimicrobial Activity Of Milk Samplessupporting
confidence: 78%
“…It is worthy to mention that the antimicrobial activity of donkey milk significantly decreased (38-40%) after digestion with pepsin (2 mg/ml) and kept about 60 to 62 % of its antimicrobial activity against B. cereus and S. aurous, respectively, suggesting that the fatty acids of donkey milk has the majority of the antimicrobial effect ( Figure 2). Similar results were reported that monoglycerides of fatty acids possessed the most potent antimicrobial activity against S. aureus [19]. It has been indicated that, donkey's native and digested milk have different effects against two pathogenic bacterial strains; Escherichia coli and Listeria monocytogenes [20].…”
Section: Chemical Composition and Antimicrobial Activity Of Milk Samplessupporting
confidence: 78%
“…Furthermore, the foam stabilities of capryloyl ester and raffinose monoesters were significantly less because the foam layer disappeared within 10 min at all concentrations; thus the carbon chain and hydrophobic group were critical factors. The foam stability of sucrose monoester was improved by increasing the carbon chain length, which indicated that the surface‐adsorbed molecules of sugar esters with longer carbon chain enhanced interaction with each other . The foam stability was also influenced by the concentrations of monoester aqueous solution, whereas low concentrations had significantly higher rates of decreasing foam layer ( P < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic properties including the molecular electron cloud shape also affects the antimicrobial activity of fatty acids and derivatives against Staphylococcus aureus, which influences MIC values [29].…”
Section: Anticandidal and Antioxidant Activitymentioning
confidence: 99%